CMM emission laws and the sub-source drainage methods in coal mining: a case study in Yuwu coal mine, Northeastern Qinshui basin, China. Issue 1 (31st March 2022) - Xu, Chao; Guo, Chaofei; Wang, Kai; Fu, Qiang; Li, Xiaofang
ABSTRACT: With the expansion of the coal mining depth and scales, the content of coal mine methane (CMM) is increasing, bringing the great challenge to the safe coal mining and greenhouse gas control. Researching CMM emission laws and its drainage technologies in underground coal mining is essential. This paper analyzed the sources of CMM emission in the workface and then put forward the grid method to measure the CMM emission laws in the single coal seam, which error was verified by the integral method. The CMM emission laws of the S2107 workface of the Yuwu mine, northeastern Qinshui basin, China were researched as a case study and it is found that the upper corner was the key position of CMM control in the workface. The sub-source CMM drainage methods by the strike high-level roadway and long vertical buried pipes were applied against the different CMM sources in the S2107 workface. The gas concentration in the return air was less than 0.6% during the CMM drainage, verifying the effectiveness of the sub-source CMM drainage methods.